EPISENTRUM PENDIDIKAN AKHLAK: BALAS DENDAM TERBAIK ADALAH MENJADIKAN DIRIMU LEBIH BAIK - Muntaha, Darul; El Syam, Robingun Suyud (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Islam is a religion that emphasizes compassion, justice, and peace, not revenge, but avoiding it is not easy. This study aims to analyze the epicenter of moral education regarding the best revenge is to make yourself better. The study uses a quantitative approach with descriptive analysis. The findings of the study show that the best revenge is to make yourself better is a popular expression often associated with Ali bin Abi Thalib. This concept emphasizes the best way to deal with someone who has hurt or harmed, by continuing to develop oneself, improving quality, and becoming a better person, not by taking revenge or leading them into badness. Becoming better is an elegant and dignified form of revenge, which shows that someone is able to rise and turn negative situations into opportunities for growth. This finding is expected to be a new perspective on how to make something negative into effective energy to teach the values ​​of Islamic education that are soothing and inspire students to become someone who is easy to forgive considering the final results that are reaped from the fruits of patience.